Creep damage analysis and numerical simulation on oil well steel pipe casing at elevated temperatures / Sarmad Khubaib Sarajun Hoda - Sarmad Khubaib, Sarajun Hoda (2021)
The purpose of this study was to investigate the Creep Damage Analysis and Numerical Simulation on Oil Well Steel Pipe casing at Elevated Temperatures using ANSYS (Computational Structural Analysis). Creep deformation is a type of plastic deformation of solid materials which occurs under high constant stress at high temperatures. Primary purpose of an Oil Well casing is to transport crude oil to the surface as well as separates the fluid or solid of inside the wellbore from the outside environment, whether in solid or in water. Casings of an oil well can experience tremendous pressure change during hydraulic fracturing processes or steam injection processes. The operating loads added with harsh conditions deep beneath the ground or in seawater exerts very high stresses on casings throughout their lifetime Analysis suggest that numerous failures of the casings have been scrutinised, however they only shed minor lights in terms on how these failures occur in terms of the life. Wellhead uplift was detected among some oil wells, and development of offshore thermal recovery technology could be restricted by the serious safety problems behind. This paper is based on the specific operating conditions of one oil well in the trial block, and the simulation calculation of casing elongation and wellhead uplift are conducted by using finite element analysis. The total casing elongation calculated is 4.2 cm. According to the research, we concluded that the wellhead uplift is caused by upper casing elongation. 88% of the total elongation happens in the air and seawater sections. Elongation is lesser in strata and the casing string below 360 m can be considered as anchored. The maximum total deformation was 1.4645 x 10-7m, average elastic strain was 1.084 x 10-8 m/m, whereas the average volumetric change is 0.30042 m3.